A biodegradable and antimicrobial polymer coating for metal implants for the prevention of prosthetic joint infection - Tiancheng Luo; Matthew P Wylie; Colin P McCoy (University of Huddersfield Press, 2022)
The aim of this project is to produce antibiotic-loaded poly (lactic-co-glycolic acid) (PLGA) polymer films by airbrush onto orthopaedic implants to address prosthetic joint infections (PJIs). It covered the development of an airbrush spray-coating technique, the selection and assessment of polymers and antibiotics, sample characterisation and antibacterial studies. The initial results are encouraging as the PLGA coatings exhibited a sustained drug release pattern and antibacterial ability against causative pathogens. Moreover, these PLGA coatings also possessed rapid degradation within 4 weeks which could provide favourable conditions for osseointegration. Furthermore, cytotoxicity assessment of final coatings will need to be conducted to ensure biocompatibility, as well as to determine the effect of each coating on osseointegration. Finally, the development of alternative coating techniques which are more cost-effective and suitable for large-scale production might be the direction of future research.